Sistema integrado de gestión de Talento Humano para mejorar el desempeño laboral en la Federación Deportiva del Carchi - Sandoval Hidalgo, Lorena Jakeline (2015)
become increasingly productive and competitive with a view to leading a scenario of sustainable development in a society; even more so if it is considered that Human Talent plays a leading role in the development of strategic and operational Human Talent activities in order to improve the performance of each of the members of the Carchi Sports Federation. It is formulated under the Competitiveness research line, "strategic and operational administration that guides each research activity." The object of Human Talent Management Research and its field of action is Human Talent Management Planning research: an integrated human talent management system and the level of performance; from which each theme is derived in order to build a novel scientific framework that explains that human talent management Chapter II establishes the methodological framework, detailing the modality, types, methods, techniques, and research instruments. The application of research instruments allows for the collection of relevant information to diagnose the current situation and the level of performance of the institution's personnel. It concludes with Chapter II, which determines the elements of the proposal as a possible solution to the problem at hand. These are: human talent planning, job descriptions and evaluations, training, professional development, and performance evaluation, all of which are reinforced by defined documents for each phase of the system. This document concludes with the research results and recommends their implementation to improve performance at the FDC.